Cognitive impairment mediates the association between sarcopenic obesity and daily living ability in the frail older population - Hang Li; Haifei Shen; Lei Yu; Yao Wen; Dan Ren; Cong Ding; Xiaobo Wang; Wanjun Xie; Yongwang Miao; Wenxu Zheng (Experimental Gerontology, 2025)
Objective: To explore the relationships between sarcopenic obesity, cognitive function, and daily living ability in a hospitalized frail older population. Method: We enrolled 206 older adults hospitalized frail or prefrail patients aged ≥60 years for body composition analysis, motor and cognitive function assessment, and daily living ability assessment. Cognitive impairment and daily living ability were measured using the Mini-Mental State Examination (MMSE) and Barthel Index (BI) score, respectively. Sarcopenia was diagnosed according to the Asian Working Group for Sarcopenia 2019 consensus. Obesity was defined by body mass index (BMI) (≥ 28 kg/m2) or body fat mass percentage (≥ 60th percentile in each sex group). Participants were divided into normal (N), simple obesity (O), sarcopenia(S), and sarcopenic obesity (SO) groups. We used correlation analysis, multiple logistic regression analysis, and mediation analysis to assess the associations between sarcopenic obesity, cognitive function and daily living ability. Results: The SO group had the highest prevalence of cognitive impairment and life activity dependency. Correlation analysis showed that the MMSE score was positively correlated with the BI score (r = 0.61, P < 0.01). The MMSE score was positively correlated with the physical performance and negatively correlated with obesity indicators (P < 0.01). According to our mediation analysis, SO and BI score had significant direct effects (coefficients = 10.13, 95 % CI: 5.76–14.50) and total effects (coefficients = 17.44, 95 % CI: 12.65–22.23). When cognitive impairment (MMSE<27) was added to the model, cognitive impairment still had an indirect (i.e., mediating) effect on the relationship between SO and BI score (coefficients = 7.31, 95 % CI: 4.05–11.11), and 41.92 % of the total effect was attributable to mediation by cognitive impairment. Conclusion: Sarcopenic obesity is closely related to cognitive impairment and decreased daily living ability. Sarcopenic obesity can affect daily living ability through the mediating effect of cognitive impairment. Therefore, more attention should be paid to the evaluation and intervention of cognitive function in order to improve the daily living ability of the older adults population with sarcopenic obesity.